2002
DOI: 10.1046/j.1365-2672.2002.01781.x
|View full text |Cite
|
Sign up to set email alerts
|

A Methylobacterium-like organism from algal crusts covering silicone rubber electric insulators in Africa

Abstract: Aims:The primary goals of this study were to isolate, identify and characterize culturable bacteria living in a close association with microalgae within green crusts covering silicone rubber electric insulators in Tanzania. Methods and Results: Twenty-four bacterial colonies were isolated from an Apatococcus crust. Characterization by statistical analyses of total cellular protein profiles demonstrated that they were highly similar to one another. Final identification was achieved using 16S rDNA sequencing and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Roseobacter had a higher abundance in the bloom area on day 3 (5.6 ± 0.49%), when algal density was lowest, but this is not as high as has been observed in other studies 11 18 72 73 . Most of the unique bacterial genera that appeared only in the bloom area are known to be associated with algal blooms: Winogradskyella is heterotrophic and many isolates are associated with algae 74 75 and phytoplankton blooms 76 ; Aureispira was was found during a Microcystis bloom 77 ; SAR202 clade organisms are ubiquitous and they usually occur in mesopelagic and deeper zones 78 79 , their appearance in the surface water of bloom areas indicate their presence is closely associated with DOM levels 78 ; Rheinheimera shows anti-algal activity 80 ; Roseovarius 81 and Bacillus 82 are also shown to have algicidal activity; Rickettsia 83 , Hoeflea 84 and Methylobacterium 85 can be symbiotic in algae; Dinoroseobacter may have a beneficial relationship with algae 86 and can be a symbiont of dinoflagellates 87 ; and Colwellia plays a key role in remineralizing organic matter generated from primary production 88 .…”
Section: Discussionmentioning
confidence: 99%
“…Roseobacter had a higher abundance in the bloom area on day 3 (5.6 ± 0.49%), when algal density was lowest, but this is not as high as has been observed in other studies 11 18 72 73 . Most of the unique bacterial genera that appeared only in the bloom area are known to be associated with algal blooms: Winogradskyella is heterotrophic and many isolates are associated with algae 74 75 and phytoplankton blooms 76 ; Aureispira was was found during a Microcystis bloom 77 ; SAR202 clade organisms are ubiquitous and they usually occur in mesopelagic and deeper zones 78 79 , their appearance in the surface water of bloom areas indicate their presence is closely associated with DOM levels 78 ; Rheinheimera shows anti-algal activity 80 ; Roseovarius 81 and Bacillus 82 are also shown to have algicidal activity; Rickettsia 83 , Hoeflea 84 and Methylobacterium 85 can be symbiotic in algae; Dinoroseobacter may have a beneficial relationship with algae 86 and can be a symbiont of dinoflagellates 87 ; and Colwellia plays a key role in remineralizing organic matter generated from primary production 88 .…”
Section: Discussionmentioning
confidence: 99%
“…Four of the seven bacterial isolates tested in this study (namely Pseudomonas putida 15 ⁄ TGE5, Serratia plymutica 23 ⁄ TGE5, Pseudomonas corrugata 31 ⁄ TGE5 and Methylobacterium radiotolerans 56 ⁄ TGF10, are well known for their plant-growth promoting or antagonistic properties against plant pathogens (Guo et al 2007;Kai et al 2007;Trifonova et al 2009;Zarnowski et al 2002). Hence, these organisms are very promising for use in TGF ⁄ potting mix applications (Trifonova et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Often, such bacteria may take profit of the presence of the fungus, as the latter organism may provide novel ecological (growth and colonization) opportunities for them. For instance, soil bacteria can benefit from the presence of fungal hyphae, as a result of the presence of fungal-released compounds, such as trehalose, oxalate and mannitol, which may serve as nutrient sources (Andrade et al 1997;Nurmiaho-Lassila et al 1997;Zarnowski et al 2002). The bacteria that associate with fungi may even obtain their benefit at the expense of the fungus, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…These four bacteria, i.e. P. putida, Stenotrophomonas plymutica, P. corrugata and M. radiotolerans , are all known for their antagonistic properties against plant pathogens (Zarnowski et al , 2002; Guo et al , 2007; Kai et al , 2007). Thus, the results of our research showed that a microbial community with the capacity to remove phytotoxic compounds from TGE and the potential to promote plant growth or plant health was selected.…”
Section: Discussionmentioning
confidence: 99%